Exploring quality of life through an online international collaboration. Issue 5 (20th October 2018) - Lock, Jennifer; Duggleby, Sandra
ABSTRACT: In today's classrooms, learning does not have to be bounded by physical space. By having access to a range of digital communication technologies, students and teachers can synchronously and asynchronously engage in authentic learning opportunities extending beyond the local community. They can be learning and interacting with others from around the world. This occurred with Grade 3 students from a school in Alberta, Canada, and Lima, Peru who investigated how their physical environments influence their quality of life. Over a seven-week period, the two groups engaged in synchronous and asynchronous activities in addressing this topic. A case study approach was used to research the project. Four key findings emerged from the data to inform teaching practice for designing and facilitating online international collaborative learning.